2012
DOI: 10.1007/s13191-012-0187-9
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Rehabilitation of a Hemisected Maxillary Molar: A Rare Entity

Abstract: Gingival recession beyond grade III and grade IV level involving furcation defects can lead to tooth loss if not intervened at appropriate time. The treatment options include scaling and root planing, Furcation-plasty, Tunnel preparation, Root separation and resection. The chief complaint of the patient was pain in the upper left first molar because of grade III furcation involvement. Since it was a four rooted molar, the treatment of choice was hemisection of the tooth and extraction of the distal half follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Scientific evidences showed that the maturation of periodontal tissues occurs after three months of the surgery [11]. In radicular hemisection, hybrid prosthesis is used; include an endodontic treatment and prosthetic rehabilitation [12]. In this case report we used a hybrid prosthetics with a prosthetic and endodontic treatment in mesial root and distal root hemisection.…”
Section: Discussionmentioning
confidence: 97%
“…Scientific evidences showed that the maturation of periodontal tissues occurs after three months of the surgery [11]. In radicular hemisection, hybrid prosthesis is used; include an endodontic treatment and prosthetic rehabilitation [12]. In this case report we used a hybrid prosthetics with a prosthetic and endodontic treatment in mesial root and distal root hemisection.…”
Section: Discussionmentioning
confidence: 97%
“…[ 4 ] It was found that it can provide a desirable long-term prognosis, especially when a restoration with accurate fit and occlusion is fabricated. [ 5 ] Bühler suggested that before extraction of any molar, hemisection should be considered as a possible treatment modality. [ 6 ] There are many studies about survival rate and success of root resected teeth.…”
Section: Discussionmentioning
confidence: 99%